2019
DOI: 10.3390/molecules25010048
|View full text |Cite
|
Sign up to set email alerts
|

A New LC-MS/MS Method for Simultaneous and Quantitative Detection of Bisphenol-A and Steroids in Target Tissues: A Power Tool to Characterize the Interference of Bisphenol-A Exposure on Steroid Levels

Abstract: Bisphenol A (BPA), an endocrine disruptor, may affect in situ steroidogenesis and alter steroids levels. The present work proposes a liquid chromatography tandem mass spectrometry method to simultaneously quantify BPA, 17β-Estradiol and testosterone in two target tissues: testis and visceral fat mass. Analytes were isolated and lipophilic impurities removed by two serial steps: liquid-liquid and solid phase extraction. All compounds were separated in a single gradient run by Kinetex F5 column and detected via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 57 publications
3
15
0
Order By: Relevance
“…On the contrary, the lower number of motile SPZ was realistically ascribable to a local accumulation and action of BPA in the epididymal caput region. In agreement, the differential accumulation of endocrine disruptors, including BPA, has been reported in different animal tissues [34] including the visceral fat mass, which in our exposure experimental model preferably accumulates BPA [35]. Interestingly, the gestational BPA exposure adversely affects spermatogenesis in adulthood mice.…”
Section: International Journal Of Endocrinologysupporting
confidence: 89%
“…On the contrary, the lower number of motile SPZ was realistically ascribable to a local accumulation and action of BPA in the epididymal caput region. In agreement, the differential accumulation of endocrine disruptors, including BPA, has been reported in different animal tissues [34] including the visceral fat mass, which in our exposure experimental model preferably accumulates BPA [35]. Interestingly, the gestational BPA exposure adversely affects spermatogenesis in adulthood mice.…”
Section: International Journal Of Endocrinologysupporting
confidence: 89%
“…In agreement with aromatase expression and physiological levels of testicular E 2 [33,54], results showed that CB1 gene deletion reduced intra-testicular estrogens levels. E 2 levels decreased bỹ 40% in CB1 -/vs.…”
Section: Discussionsupporting
confidence: 78%
“…In animal models, the accumulation of BPA in foetuses and offspring during the foetal/neonatal period has been demonstrated to depend on the maternal exposure and to be mediated by the placenta or breast milk [ 11 , 12 ], as the efficient drug-metabolising systems of the mothers is slightly altered during pregnancy [ 13 , 14 , 15 ]. This accumulation occurs since the offspring acquire only late after birth the ability to metabolize BPA, quite late after birth [e.g., 21 days post partum ( dpp ) in rat] [ 16 ] thus introducing a large measure of uncertainty in any risk assessment that is exclusively based on dose-effect observations, not considering the real accumulation of BPA that also depends on variations in individual susceptibility [ 17 ]. Indeed, three hazard doses for BPA exposure were defined: tolerable daily intake (TDI; 50 μg/kg body weight (bw)/day, indicated as safe reference dose for human), no-observed-adverse-effect-level (NOAEL; 5 mg/kg bw/day), and lowest-observed-adverse-effect level (LOAEL; 50 mg/kg bw/day) [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…More interesting is that both modulate either the progression of spermatogensis and the adiposity of epididymal fat (perigonadal epididymal withe tissue, pEWAT) [ 42 , 43 , 44 , 45 ], tracing a potential harmful effect of BPA on germ cells which could also result from the impairment of nearby pEWAT. Notably, BPA accumulates in fat tissue [ 1 , 12 , 17 , 46 , 47 , 48 , 49 ], it targets gene expression of enzymes metabolizing endocannabinoids [ 1 , 50 , 51 , 52 , 53 ] and steroids [ 54 , 55 ] and its accumulation in fat tissue is related to steroid levels [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation